Cable connector assembly - WU JERRY (2013)
A cable assembly (100) includes a housing having a mounting section, a retaining cavity defined in an interior side of the mounting section, and a mounting cavity (1030) defined in an external side of the mounting section. An ejection mechanism is assembled to the housing, the ejection mechanism including a slider (4) mounted to the housing, a bail (3) assembled to the mounting section and engaged with the slider. The bail (3) has a transverse handle portion (30) accommodated in the mounting cavity (1030) and a pair of driving arms (31) connected to the handle portion and pivotally engaged with the housing to cause outward movement of ejector (5) to separate the cable assembly from a mating receptacle. A cable (8) includes a number of wires (85), an inner layer (83) enclosing the wires, a metallic braiding (84) shielding the inner layer, and an outer jacket (81) covering the metallic braiding. A second ring (92) is mounted between the metallic braiding and the inner layer. A first ring (91) is crimped onto an